Platinum(II) Complexes Bearing Triphenylphosphine and Chelating Oximes: Antiproliferative Effect and Biological Profile in Resistant Cells. (16th June 2020) - Hyeraci, Mariafrancesca; Colalillo, Marialuigia; Labella, Luca; Marchetti, Fabio; Samaritani, Simona; Scalcon, Valeria; Rigobello, Maria Pia; Dalla Via, Lisa
Abstract: Platinum(II) complexes of the type [Pt(Cl)(PPh3 )(κ 2 ‐ N, O )‐(1C(R)=N(OH)‐2(O)C6 H4 )] with R=Me, H, (1 and 2 ) were synthesized and characterized. Single‐crystal X‐ray diffraction confirmed the proposed ( SP 4‐3) configuration for 1 . Study of the antiproliferative activity, performed on a panel of human tumor cell lines and on mesothelial cells, highlighted complex 2 as the more effective. In particular, it showed a remarkable cytotoxicity in ovarian carcinoma cells (A2780) and interestingly, a significant antiproliferative effect on cisplatin resistant cells (A2780cis). Investigation into the intracellular mechanism of action demonstrated that 2 had a lower ability to platinate DNA than did cisplatin, which was taken as reference, and a notably higher uptake in resistant cells. A significant accumulation in mitochondria, along with the ability to induce concentration‐dependent mitochondrial membrane depolarization and intracellular reactive oxygen species production, allowed us to propose a mitochondrion‐mediated pathway as responsible for the interesting cytotoxic profile of complex 2 . Abstract : Fighting drug resistance . The Pt(II) complex efficiently enters resistant cells causing a significant antiproliferative effect, despite scant interaction with DNA. Mitochondria appear a possible target. Mitochondrial membrane depolarization and oxidative stress seem to be responsible for cytotoxicity. This biological profile could represent a model for the development of promising anticancer drugs.